Pendampingan Belajar Anak-Anak Membaca Al-Qur’an dengan Ilmu Tajwid di Rumah Pengajian Ibu Gabena Harahap Lingkungan IV Kelurahan Pasar Sibuhuan - Lina Mayasari Siregar; Irma Suryani Siregar; Nur Fitryani Siregar (Sekolah Tinggi Agama Islam Barumun Raya (STAI BR) Sibuhuan, 2023)
Mother Gabena Harahap's recitation place is a place to learn the Koran for children of the Sibuhuan Market neighborhood VI community for those who want to learn the Koran in neighborhood VI of Sibuhuan Pasar Village. However, there is a problem that is still a problem in terms of reading, namely the lack of applying the correct knowledge of recitation. Children who recite the Koran only apply the pronunciation of hijaiyah letters without applying the knowledge of recitation. The purpose of this activity is to provide learning to children who recite the Koran so that their reading is in accordance with the science of recitation. The method used in the mentoring is face-to-face teaching of the Koran to children who recite the Koran at the Gabena Harahap Study House. The result of the service is an increase in the ability to read the Koran with recitation.